1995
DOI: 10.1073/pnas.92.9.3918
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and synaptic properties of embryonic luteinizing hormone-releasing hormone neurons in explant cultures.

Abstract: Voltage-and ligand-activated channels in embryonic neurons containing luteinizing hormone-releasing hormone (LHRH) were studied by patch-pipette, whole-cell current and voltage clamp techniques. LHRH In mammals, luteinizing hormone (LH) pulses are closely correlated with increased activities in as yet unidentified mediobasal hypothalamic neurons (1-3) which are believed to regulate the secretory activities of LH-releasing hormone (LHRH)-containing neurons. Due to the small number of LHRH neurons in brain, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
139
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(148 citation statements)
references
References 31 publications
9
139
0
Order By: Relevance
“…1 B). The small amount of current required to initiate action potential firing is consistent with the high input resistance of these cells (Kusano et al, 1995;Spergel et al, 1999;Suter et al, 2000b;DeFazio and Moenter, 2002;Kuehl-Kovarik et al, 2002). There was little evidence of spike frequency adaptation over the 500 ms injection, although a slight decrement in spike amplitude was routinely observed.…”
Section: Gnrh Neurons Exhibit Homogeneous Firing Propertiesmentioning
confidence: 60%
“…1 B). The small amount of current required to initiate action potential firing is consistent with the high input resistance of these cells (Kusano et al, 1995;Spergel et al, 1999;Suter et al, 2000b;DeFazio and Moenter, 2002;Kuehl-Kovarik et al, 2002). There was little evidence of spike frequency adaptation over the 500 ms injection, although a slight decrement in spike amplitude was routinely observed.…”
Section: Gnrh Neurons Exhibit Homogeneous Firing Propertiesmentioning
confidence: 60%
“…Therefore, taking advantage of the extra-CNS origin of these cells, several groups have established an in vitro model of postmitotic, primary GnRH-1 cells in nasal explants. Individual GnRH-1 neurons in nasal explants exhibit electrical and synaptic properties similar to in vivo GnRH-1 neurons, including responses to GABAergic and glutamatergic stimulation (Kusano et al, 1995). In addition to depolarized-induced GnRH-1 release (Terasawa et al, 1999a;Moore and Wray, 2000), as in vivo, GnRH-1 neurons in nasal explants release GnRH-1 in a pulsatile manner (Terasawa et al, 1999a;Funabashi et al, 2000) with the interpulse interval being species dependent.…”
Section: Introductionmentioning
confidence: 98%
“…Previous electrophysiological studies have demonstrated the presence of I K , I A , and I IR , as well as low-and high-thresholdactivated calcium conductances, in immortalized GT1 cells (Bosma, 1993;Hales et al, 1994;Van Goor et al, 1999a,b) and cultured embryonic GnRH neurons of the mouse (Kusano et al, 1995). Although detailed information on the basic membrane properties of green fluorescent protein (GFP)-expressing GnRH neurons is not yet available, it is interesting to note that outward potassium currents indicative of I A and I K conductances were reported by Spergel and colleagues (1999).…”
Section: Heterogeneity Within the Adult Gnrh Neuronal Populationmentioning
confidence: 99%